Microstructure and mechanical properties of the TiZrNbMoTa refractory high-entropy alloy produced by mechanical alloying and spark plasma sintering. (December 2020) - Zhu, Chenglong; Li, Zhanjiang; Hong, Chunfu; Dai, Pinqiang; Chen, Junfeng
Abstract: The equiatomic refractory high entropy alloy (HEA) TiZrNbMoTa was investigated. The alloyed powders with face-centered cubic (FCC) structured solid solution phase were prepared by mechanical alloying (MA) and then sintered by spark plasma sintering (SPS) at 1300, 1400, 1500, and 1600 °C. The microstructure and mechanical properties of the bulk alloy were investigated. The body-centered cubic (BCC) structured solid solution phase and the ZrO2 phase precipitated from the FCC structured solid solution phase during cool-down from sintering. The highest compression fracture strength (3759 MPa) and fracture strain (12.1%) were obtained in the refractory HEA sintered at 1400 °C. The grain boundary strengthening, precipitation strengthening, solid solution strengthening, transformation-induced plastic (TRIP) effect, and toughening effect of the ZrO2 phase are the important factors for the high strength and ducitily of the refractory HEA prepared in this study. Highlights: TiZrNbMoTa refractory HEA was prepared by powder metallurgy (MA and SPS). The TiZrNbMoTa refractory HEA with dual-phase (FCC and BCC) solid solution structure was successfully prepared. TiZrNbMoTa refractory HEA exhibits excellent mechanical properties superior than the refractory HEAs prepared by arc-melting.